Hydrogen-Rich Saline Protects against Ischemia/Reperfusion Injury in Grafts after Pancreas Transplantations by Reducing Oxidative Stress in Rats - Zhu-Lin Luo; Long Cheng; Jian-Dong Ren; Chen Fang; Ke Xiang; Hao-Tong Xu; Li-Jun Tang; Tao Wang; Fu-Zhou Tian (Mediators of Inflammation)
Purpose. This study aimed to investigate the therapeutic potential of hydrogen-rich saline on pancreatic ischemia/reperfusion (I/R) injury in rats. Methods. Eighty heterotopic pancreas transplantations (HPT) were performed in syngenic rats. The receptors were randomized blindly into the following three groups: the HPT group and two groups that underwent transplantation and administration of hydrogen-rich saline (HS, >0.6 mM, 6 mL/kg) or normal saline (NS, 6 mL/kg) via the tail vein at the beginning of reperfusion (HPT + HS group, HPT + NS group). Samples from the pancreas and blood were taken at 12 hours after reperfusion. The protective effects of hydrogen-rich saline against I/R injury were evaluated by determining the changes in histopathology and measuring serological parameters, oxidative stress-associated molecules, and proinflammatory cytokines. Results. Administration of hydrogen-rich saline produced notable protection against pancreatic I/R injury in rats. Histopathological improvements and recovery of impaired pancreatic function were observed. In addition, TNF-α, IL-1β, and IL-6 were reduced markedly in the HPT + HS group. Additionally, there were noticeable inhibitory effects on the pancreatic malondialdehyde level and considerable recruitment of SOD and GPx, which are antioxidants. Conclusion. Hydrogen-rich saline treatment significantly attenuated the severity of pancreatic I/R injury in rats, possibly by reducing oxidative stress and inflammation.